Influence of Hydrocarbon Additives on the Velocity of Detonation Wave and Detonation Limits in Lean Mixes by the Example of The Reaction of Hydrogen Oxidation - Rubtsov, N.M (International Journal of Natural Sciences Research, 2016)
The formalism of the one-dimensional detonation theory taking into account both thermal losses and the theory of branched chain processes was applied to hydrogen oxidation in the presence of hydrocarbon additive. It is shown that accounting for both reactions of termination of the active centers of combustion via molecules of hydrocarbon additive, and chain oxidation of hydrocarbon additive allows qualitative interpreting of the main features of the process. They are both passing of detonation velocity through a maximum at an increase in content of the additive in lean mix and the existence of two detonation limits on the concentration of the additive.